Absence of AGG Interruptions Is a Risk Factor for Full Mutation Expansion Among Israeli FMR1 Premutation Carriers - Domniz, Noam; Ries-Levavi, Liat; Cohen, Yoram; Marom-Haham, Lilach; Berkenstadt, Michal; Pras, Elon; Glicksman, Anne; Tortora, Nicole; Latham, Gary J.; Hadd, Andrew G.; Nolin, Sarah L.; Elizur, Shai E. (Frontiers in Genetics, 2018)
Introduction: Fragile X syndrome (FXS) is a common form of X-linked intellectual and developmental disability with a prevalence of 1/4000 - 5000 in males and 1/6000 - 8000 in females. Most cases of the syndrome result from expansion of a premutation (55-200 CGGs) to a full mutation (>200 CGGs) repeat located in the 5' untranslated region of the fragile X mental retardation (FMR1) gene. The risk for full mutation expansions increases dramatically with increasing numbers of CGG repeats. Recent studies, however, revealed AGG interruptions within the repeat function as a "protective factor" decreasing the risk of intergenerational expansion. Material and Methods: This study was conducted to validate the relevance of AGG analysis for the ethnically diverse Israeli population. To increase the accuracy of our results, we combined results from Israel with those from the New York State Institute for Basic Research in Developmental Disabilities (IBR). To the best of our knowledge this is the largest cohort of different ethnicities to examine risks of unstable transmissions and full mutation expansions among FMR1 premutation carriers. Results: The combined data included 1471 transmissions of maternal premutation alleles: 369 (25.1%) stable and 1,102 (74.9%) unstable transmissions. Full mutation expansions were identified in 20.6% (303/1471) of transmissions. A total of 97.4% (388/397) of transmissions from alleles with no AGGs were unstable, 79.6% (513/644) in alleles with 1 AGG and 46.7% (201/430)) in alleles with 2 or more AGGs. The same trend was seen with full mutation expansions where 40% (159/397) of alleles with no AGGs expanded to a full mutation, 20.2% (130/644) for alleles with 1 AGG and only 3.2% (14/430) in alleles with 2 AGGs or more. None of the alleles with 3 or more AGGs expanded to full mutations. Conclusion: We recommend that risk estimates for FMR1 premutation carriers be based on AGG interruptions as well as repeat size in Israel and worldwide.